Potensial Antimalaria dan Antioxidan Ekstrak Metanol Daun kayu titi (Alstonia sp) - Maria Nindatu; Matha Kaihena; Adriana Hieriej; Amos Killay; Hery Jotlely (Postgraduate, University of Mataram, 2023)
Alstonia sp leaves extract has previously been reported as a potential antimalarial drug as traditional. This study aims to analyze the antimalarial activity and determine the antioxidant potential of titi tree leaves (Alstonia sp). The method used in this research is a modified method of